The Global Financial Crisis and Its Impact on Indian Capital Market - Islam, Aminul (Indian Journal of Finance, 2009)
The Global financial crisis has occurred several times .The US administration and Congress are creating a $700 billion rescue-package to resolve the worst financial crisis since the Great Depression of 1930s.In 1942, Winston Churchill's commented, "This is not the end. It is not even the beginning of the end. But it is, perhaps, the end of the beginning. The financial crunch that began in mid-2007 has worsened so dramatically that all politicians have agreed to a government rescue. In that sense, we have reached the end of the beginning of the current drama.But two major chapters are yet to unfold. The first relates to problems that will hamstring, and maybe doom the rescue. The second relates to the global recession that has probably started, and will hit countries like India far harder than mere the Wall Street turmoil.